Teaching About Evolution and the Nature of Science - National Academy of Sciences (The National Academies Press, 1998)
Today many school students are shielded from one of the most important concepts in modern science: evolution. In engaging and conversational style, Teaching About Evolution and the Nature of Science provides a well-structured framework for understanding and teaching evolution. Written for teachers, parents, and community officials as well as scientists and educators, this book describes how evolution reveals both the great diversity and similarity among the Earth's organisms; it explores how scientists approach the question of evolution; and it illustrates the nature of science as a way of knowing about the natural world. In addition, the book provides answers to frequently asked questions to help readers understand many of the issues and misconceptions about evolution. The book includes sample activities for teaching about evolution and the nature of science. For example, the book includes activities that investigate fossil footprints and population growth that teachers of science can use to introduce principles of evolution. Background information, materials, and step-by-step presentations are provided for each activity. In addition, this volume:
Keywords: Education; Biology and Life Sciences

Darwin's Gift to Science and Religion - Ayala, Francisco J. (The National Academies Press, 2007)
With the publication in 1859 of On the Origin of Species by Means of Natural Selection, Charles Darwin established evolution by common descent as the dominant scientific explanation for nature's diversity. This was to be his gift to science and society; at last, we had an explanation for how life came to be on Earth. Scientists agree that the evolutionary origin of animals and plants is a scientific conclusion beyond reasonable doubt. They place it beside such established concepts as the roundness of the earth, its revolution around the sun, and the molecular composition of matter. That evolution has occurred, in other words, is a fact. Yet as we approach the bicentennial celebration of Darwin's birth, the world finds itself divided over the truth of evolutionary theory. Consistently endorsed as "good science" by experts and overwhelmingly accepted as fact by the scientific community, it is not always accepted by the public, and our schools continue to be battlegrounds for this conflict. From the Tennessee trial of a biology teacher who dared to teach Darwin's theory to his students in 1925 to Tammy Kitzmiller's 2005 battle to keep intelligent design out of the Dover district schools in Pennsylvania, it's clear that we need to cut through the propaganda to quell the cacophony of raging debate. With the publication of Darwin's Gift, a voice at once fresh and familiar brings a rational, measured perspective to the science of evolution. An acclaimed evolutionary biologist with a background in theology, Francisco Ayala offers clear explanations of the science, reviews the history that led us to ratify Darwin's theories, and ultimately provides a clear path for a confused and conflicted public.
Keywords: Biology and Life Sciences; Explore Science

How Students Learn: Science in the Classroom - National Research Council (The National Academies Press, 2005)
How Students Learn: Science in the Classroom builds on the discoveries detailed in the best-selling How People Learn. Now these findings are presented in a way that teachers can use immediately, to revitalize their work in the classroom for even greater effectiveness. Organized for utility, the book explores how the principles of learning can be applied in science at three levels: elementary, middle, and high school. Leading educators explain in detail how they developed successful curricula and teaching approaches, presenting strategies that serve as models for curriculum development and classroom instruction. Their recounting of personal teaching experiences lends strength and warmth to this volume. This book discusses how to build straightforward science experiments into true understanding of scientific principles. It also features illustrated suggestions for classroom activities.
Keywords: Education

Workshop on Biotechnology in Agriculture: Summary Report, Jakarta, Indonesia, March 13-14, 1986 - National Research Council (The National Academies Press, 1986)
Keywords: Agriculture

Searching for Life Across Space and Time: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The search for life is one of the most active fields in space science and involves a wide variety of scientific disciplines, including planetary science, astronomy and astrophysics, chemistry, biology, chemistry, and geoscience. In December 2016, the Space Studies Board hosted a workshop to explore the possibility of habitable environments in the solar system and in exoplanets, techniques for detecting life, and the instrumentation used. This publication summarizes the presentations and discussions from the workshop.
Keywords: Space and Aeronautics

How Students Learn: History, Mathematics, and Science in the Classroom - National Research Council (The National Academies Press, 2005)
How do you get a fourth-grader excited about history? How do you even begin to persuade high school students that mathematical functions are relevant to their everyday lives? In this volume, practical questions that confront every classroom teacher are addressed using the latest exciting research on cognition, teaching, and learning. How Students Learn: History, Mathematics, and Science in the Classroom builds on the discoveries detailed in the bestselling How People Learn. Now, these findings are presented in a way that teachers can use immediately, to revitalize their work in the classroom for even greater effectiveness. Organized for utility, the book explores how the principles of learning can be applied in teaching history, science, and math topics at three levels: elementary, middle, and high school. Leading educators explain in detail how they developed successful curricula and teaching approaches, presenting strategies that serve as models for curriculum development and classroom instruction. Their recounting of personal teaching experiences lends strength and warmth to this volume. The book explores the importance of balancing students' knowledge of historical fact against their understanding of concepts, such as change and cause, and their skills in assessing historical accounts. It discusses how to build straightforward science experiments into true understanding of scientific principles. And it shows how to overcome the difficulties in teaching math to generate real insight and reasoning in math students. It also features illustrated suggestions for classroom activities. How Students Learn offers a highly useful blend of principle and practice. It will be important not only to teachers, administrators, curriculum designers, and teacher educators, but also to parents and the larger community concerned about children's education.
Keywords: Education

In the Light of Evolution: Volume III: Two Centuries of Darwin - National Academy of Sciences (The National Academies Press, 2009)
Two Centuries of Darwin is the outgrowth of an Arthur M. Sackler Colloquium, sponsored by the National Academy of Sciences on January 16-17, 2009. In the chapters of this book, leading evolutionary biologists and science historians reflect on and commemorate the Darwinian Revolution. They canvass modern research approaches and current scientific thought on each of the three main categories of selection (natural, artificial, and sexual) that Darwin addressed during his career. Although Darwin's legacy is associated primarily with the illumination of natural selection in The Origin, he also contemplated and wrote extensively about what we now term artificial selection and sexual selection. In a concluding section of this book, several science historians comment on Darwin's seminal contributions.
Keywords: Biology and Life Sciences; Explore Science

Identifying New Community-Driven Science Themes for NSF's Support of Paleoclimate Research: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Sediments, ice, corals, and trees are just some of the natural storehouses of information that help tell the complicated history of Earth’s climate. Paleoclimate researchers use these “proxies,” in combination with numerical models, to gain understanding of the magnitudes, rates, and drivers of past climate variability with the goal of informing understanding of current and future change in Earth’s climate system. The Paleo Perspectives on Climate Change (P2C2) program of the National Science Foundation (NSF) has advanced paleoclimate research through proxy development, data-model comparisons, and synthesis work, and has facilitated interdisciplinary collaboration that has contributed to the growth of the field. This new publication highlights discussions at a June 2021 workshop that focused on identifying potential future paleoclimate research directions to further advance understanding of past climate and better inform the public and decision makers about the expected future.
Keywords: Earth Sciences

Biographical Memoirs: Volume 60 - National Academy of Sciences (The National Academies Press, 1991)
Biographic Memoirs: Volume 60 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Mendel in the Kitchen: A Scientist's View of Genetically Modified Foods - Fedoroff, Nina V.; Brown, Nancy Marie (The National Academies Press, 2004)
While European restaurants race to footnote menus, reassuring concerned gourmands that no genetically modified ingredients were used in the preparation of their food, starving populations around the world eagerly await the next harvest of scientifically improved crops. Mendel in the Kitchen provides a clear and balanced picture of this tangled, tricky (and very timely) topic. Any farmer you talk to could tell you that we've been playing with the genetic makeup of our food for millennia, carefully coaxing nature to do our bidding. The practice officially dates back to Gregor Mendel—who was not a renowned scientist, but a 19th century Augustinian monk. Mendel spent many hours toiling in his garden, testing and cultivating more than 28,000 pea plants, selectively determining very specific characteristics of the peas that were produced, ultimately giving birth to the idea of heredity—and the now very common practice of artificially modifying our food. But as science takes the helm, steering common field practices into the laboratory, the world is now keenly aware of how adept we have become at tinkering with nature—which in turn has produced a variety of questions. Are genetically modified foods really safe? Will the foods ultimately make us sick, perhaps in ways we can't even imagine? Isn't it genuinely dangerous to change the nature of nature itself? Nina Fedoroff, a leading geneticist and recognized expert in biotechnology, answers these questions, and more. Addressing the fear and mistrust that is rapidly spreading, Federoff and her co-author, science writer Nancy Brown, weave a narrative rich in history, technology, and science to dispel myths and misunderstandings. In the end, Fedoroff arues, plant biotechnology can help us to become better stewards of the earth while permitting us to feed ourselves and generations of children to come. Indeed, this new approach to agriculture holds the promise of being the most environmentally conservative way to increase our food supply.
Keywords: Explore Science; Biology and Life Sciences

Lost Crops of the Incas: Little-Known Plants of the Andes with Promise for Worldwide Cultivation - National Research Council (The National Academies Press, 1989)
This fascinating, readable volume is filled with enticing, detailed information about more than 30 different Incan crops that promise to follow the potato's lead and become important contributors to the world's food supply. Some of these overlooked foods offer special advantages for developing nations, such as high nutritional quality and excellent yields. Many are adaptable to areas of the United States. Lost Crops of the Incas includes vivid color photographs of many of the crops and describes the authors' experiences in growing, tasting, and preparing them in different ways. This book is for the gourmet and gourmand alike, as well as gardeners, botanists, farmers, and agricultural specialists in developing countries.
Keywords: Agriculture; Biology and Life Sciences

(NAS Colloquium) Genetics and the Origin of Species: From Darwin to Molecular Biology 60 Years After Dobzhansky (The National Academies Press, 1997)
Keywords: Biology and Life Sciences

Perspectives on Health Equity and Social Determinants of Health - National Academy of Medicine (The National Academies Press, 2017)
Social factors, signals, and biases shape the health of our nation. Racism and poverty manifest in unequal social, environmental, and economic conditions, resulting in deep-rooted health disparities that carry over from generation to generation. In Perspectives on Health Equity and Social Determinants of Health, authors call for collective action across sectors to reverse the debilitating and often lethal consequences of health inequity. This edited volume of discussion papers provides recommendations to advance the agenda to promote health equity for all. Organized by research approaches and policy implications, systems that perpetuate or ameliorate health disparities, and specific examples of ways in which health disparities manifest in communities of color, this Special Publication provides a stark look at how health and well-being are nurtured, protected, and preserved where people live, learn, work, and play. All of our nation’s institutions have important roles to play even if they do not think of their purpose as fundamentally linked to health and well-being. The rich discussions found throughout Perspectives on Health Equity and Social Determinants of Health make way for the translation of policies and actions to improve health and health equity for all citizens of our society. The major health problems of our time cannot be solved by health care alone. They cannot be solved by public health alone. Collective action is needed, and it is needed now.
Keywords: Health and Medicine

Sociality, Hierarchy, Health: Comparative Biodemography: A Collection of Papers - National Research Council (The National Academies Press, 2014)
Sociality, Hierarchy, Health: Comparative Biodemography is a collection of papers that examine cross-species comparisons of social environments with a focus on social behaviors along with social hierarchies and connections, to examine their effects on health, longevity, and life histories. This report covers a broad spectrum of nonhuman animals, exploring a variety of measures of position in social hierarchies and social networks, drawing links among these factors to health outcomes and trajectories, and comparing them to those in humans. Sociality, Hierarchy, Health revisits both the theoretical underpinnings of biodemography and the empirical findings that have emerged over the past two decades.
Keywords: Behavioral and Social Sciences

How Students Learn: History in the Classroom - National Research Council (The National Academies Press, 2005)
How Students Learn: History in the Classroom builds on the discoveries detailed in the best-selling How People Learn. Now these findings are presented in a way that teachers can use immediately, to revitalize their work in the classroom for even greater effectiveness.
Keywords: Education

How Students Learn: Mathematics in the Classroom - National Research Council (The National Academies Press, 2005)
How Students Learn: Mathematics in the Classroom builds on the discoveries detailed in the best-selling How People Learn. Now these findings are presented in a way that teachers can use immediately, to revitalize their work in the classroom for even greater effectiveness. This book shows how to overcome the difficulties in teaching math to generate real insight and reasoning in math students. It also features illustrated suggestions for classroom activities.
Keywords: Education

Tempo and Mode in Evolution: Genetics and Paleontology 50 Years After Simpson - Fitch, Walter M.; Ayala, Francisco J. (The National Academies Press, 1995)
Since George Gaylord Simpson published Tempo and Mode in Evolution in 1944, discoveries in paleontology and genetics have abounded. This volume brings together the findings and insights of today's leading experts in the study of evolution, including Ayala, W. Ford Doolittle, and Stephen Jay Gould. The volume examines early cellular evolution, explores changes in the tempo of evolution between the Precambrian and Phanerozoic periods, and reconstructs the Cambrian evolutionary burst. Long-neglected despite Darwin's interest in it, species extinction is discussed in detail. Although the absence of data kept Simpson from exploring human evolution in his book, the current volume covers morphological and genetic changes in human populations, contradicting the popular claim that all modern humans descend from a single woman. This book discusses the role of molecular clocks, the results of evolution in 12 populations of Escherichia coli propagated for 10,000 generations, a physical map of Drosophila chromosomes, and evidence for "hitchhiking" by mutations.
Keywords: Biology and Life Sciences

Lost Crops of Africa: Volume II: Vegetables - National Research Council (The National Academies Press, 2006)
This report is the second in a series of three evaluating underexploited African plant resources that could help broaden and secure Africa's food supply. The volume describes the characteristics of 18 little-known indigenous African vegetables (including tubers and legumes) that have potential as food- and cash-crops but are typically overlooked by scientists and policymakers and in the world at large. The book assesses the potential of each vegetable to help overcome malnutrition, boost food security, foster rural development, and create sustainable landcare in Africa. Each species is described in a separate chapter, based on information gathered from and verified by a pool of experts throughout the world. Volume I describes African grains and Volume III African fruits.
Keywords: Agriculture; Biology and Life Sciences

Microbial Evolution and Co-Adaptation: A Tribute to the Life and Scientific Legacies of Joshua Lederberg: Workshop Summary - Institute of Medicine (The National Academies Press, 2009)
Dr. Joshua Lederberg - scientist, Nobel laureate, visionary thinker, and friend of the Forum on Microbial Threats - died on February 2, 2008. It was in his honor that the Institute of Medicine's Forum on Microbial Threats convened a public workshop on May 20-21, 2008, to examine Dr. Lederberg's scientific and policy contributions to the marketplace of ideas in the life sciences, medicine, and public policy. The resulting workshop summary, Microbial Evolution and Co-Adaptation, demonstrates the extent to which conceptual and technological developments have, within a few short years, advanced our collective understanding of the microbiome, microbial genetics, microbial communities, and microbe-host-environment interactions.
Keywords: Biology and Life Sciences; Health and Medicine

Biographical Memoirs: Volume 63 - National Academy of Sciences (The National Academies Press, 1994)
Biographic Memoirs: Volume 63 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

High-School Biology Today and Tomorrow - National Research Council (The National Academies Press, 1989)
Biology is where many of science's most exciting and relevant advances are taking place. Yet, many students leave school without having learned basic biology principles, and few are excited enough to continue in the sciences. Why is biology education failing? How can reform be accomplished? This book presents information and expert views from curriculum developers, teachers, and others, offering suggestions about major issues in biology education: what should we teach in biology and how should it be taught? How can we measure results? How should teachers be educated and certified? What obstacles are blocking reform?
Keywords: Education

Pesticide Resistance: Strategies and Tactics for Management - National Research Council (The National Academies Press, 1986)
Based on a symposium sponsored by the Board on Agriculture, this comprehensive book explores the problem of pesticide resistance; suggests new approaches to monitor, control, or prevent resistance; and identifies the changes in public policy necessary to protect crops and human health from the ravages of pests. The volume synthesizes the most recent information from a wide range of disciplines, including entomology, genetics, plant pathology, biochemistry, economics, and public policy. It also suggests research avenues that would indicate how to counter future problems. A glossary provides the reader with additional guidance.
Keywords: Agriculture

The Life Sciences: Recent Progress and Application to Human Affairs The World of Biological Research Requirements for the Future (The National Academies Press, 1970)
Keywords: Health and Medicine

Biographical Memoirs: Volume 47 - National Academy of Sciences (The National Academies Press, 1975)
Biographic Memoirs: Volume 47 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography